Utilization of Commercial Law to Promote Public Welfare and Legal Certainty for Business Actors - Aicha Azdina Adly Fesya; Alya Rayana Siregar; Ahmad Yani Anshori (AT-TAFAHUM: Journal of Law, 2023)
Commercial law plays a fundamental role in establishing legal certainty, protecting business actors, and promoting sustainable economic development. As commercial transactions continue to expand in both domestic and international markets, a comprehensive legal framework becomes increasingly essential to regulate business activities, prevent disputes, and ensure fair competition. This study aims to analyze the role of commercial law in enhancing legal certainty and supporting public welfare within the Indonesian legal system. The research employs a normative legal research method using statutory, historical, and comparative approaches. Data were collected through a comprehensive review of legal literature, including legislation, legal doctrines, scholarly publications, and relevant legal theories. The findings indicate that commercial law serves as a vital legal instrument governing contractual relationships, corporate activities, trade, investment, and dispute resolution. The Indonesian Commercial Code (KUHD), the Civil Code (KUH Perdata), and sector-specific legislation provide the primary legal foundation for commercial transactions. The study further reveals that the validity of contracts, as stipulated in Article 1320 of the Civil Code, together with the principles of good faith and pacta sunt servanda, plays a crucial role in maintaining legal certainty and minimizing commercial disputes. Furthermore, dispute resolution mechanisms through litigation and alternative dispute resolution, including negotiation, mediation, and arbitration, contribute significantly to efficient conflict resolution while preserving business relationships. The study concludes that the consistent implementation of commercial law not only strengthens legal protection for business actors but also fosters a favorable business climate, supports the development of micro, small, and medium enterprises (MSMEs), and contributes to sustainable economic growth and public welfare in accordance with the objectives of the 1945 Constitution of the Republic of Indonesia.